We Are Done with 'Hacking'. - Bugayenko, Yegor (Communications of the ACM, 2018)
The author argues that computer software programmers offer various skills that go beyond hacking algorithms and making data structures. Topics include a decline in the costs associated with computer equipment and memory, the growth of open source software which allows programmers to wire together available components versus writing code, and the high demand for information technology personnel such as programmers despite their increasing population size which has increased their average salaries.